Double-layer structure flexible intestinal anastomosis stent with antibacterial surface layer and preparation method thereof

The double-layer structure flexible intestinal anastomosis scaffold prepared by electrospinning technology uses the PTMC/PHA inner layer and the PVA/OHA-Gs antibacterial outer layer to solve the problems of anastomosis stenosis and inflammation in the prior art, and realizes the biological of the scaffold Compatibility and antibacterial effects simultaneously promote the intestinal healing process.

CN118924961BActive Publication Date: 2025-01-07WENZHOU AOTONG MEDICAL TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411421379.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-07
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The existing biodegradable intestinal anastomosis stents are prone to cause anastomosis stenosis, device displacement and tissue inflammation after treating intestinal diseases, and the antibacterial function is difficult to effectively exert in a short period of time and affect the subsequent healing process.

Method used

The flexible intestinal anastomosis scaffold with a double-layer structure is prepared by electrospinning technology. The inner layer is composed of PTMC and PHA blended nanofibers, and the outer layer is made of aldehyde-based hyaluronic acid and PVA blended solution and gentamicin sulfate is added to the blended solution of aldehyaluronic acid and PVA. Continuous electrospinning forms an antibacterial surface layer, combining the drug-carrying effect of Gs.

Benefits of technology

The scaffold has excellent mechanical properties, biodegradable, and promotes cell migration and proliferation. At the same time, it effectively exerts antibacterial effects during the inflammatory period, reduces the risk of infection, promotes anastomosis healing, and reduces the risk of long-term complications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118924961B_ABST
    Figure CN118924961B_ABST
Patent Text Reader

Abstract

A double-layer structured flexible intestinal anastomosis stent with an antibacterial surface layer and a preparation method thereof, wherein a PTMC and PHA co-blended spinning solution is first electrospun to obtain a nanofiber layer with excellent mechanical properties, biodegradability, and favorable for cell attachment, and then a PVA / OHA fiber layer loaded with Gs is obtained on the PTMC / PHA layer in the form of continuous electrospinning to obtain an intestinal anastomosis stent with a double-layer nanofiber structure, wherein the fiber filaments co-spun by PVA and OHA can remain in a gel state for a certain period of time in an aqueous solution, so that Gs can fully exert its antibacterial effect in the early stage of anastomosis healing, provide a relatively sterile environment for the early stage of intestinal anastomosis healing, and degrade with intestinal fluid within a period of time; thereafter, the PTMC / PHA nanofiber layer is exposed and adheres to the intestinal wall, and has good biological tissue compatibility and the effect of promoting cell migration and proliferation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomaterials, and in particular to a double-layer structured flexible intestinal anastomosis stent with an antibacterial surface layer and a preparation method thereof. Background Art

[0002] Digestive tract anastomotic leakage is a serious complication that affects intestinal tissue healing or repair during postoperative treatment of gastrointestinal diseases such as intestinal tumors and intestinal obstruction. High anastomotic tension, low blood supply or postoperative infection are the main reasons for the difficulty in healing the anastomosis and causing anastomotic leakage. In response to these problems, the implantation of biological tissue engineering scaffolds is considered to be a new way to solve intestinal anastomotic leakage. At the same time, this research field is of great significance for strengthening clinical treatment and improving the quality of life of patients.

[0003] At present, research on biodegradable anastomotic rings (BARs) based on biodegradable metals or polymers has attracted much attention. It is a degradable stent used for anastomosis after intestinal resection. For example, a reported poly(L-lactide) / paclitaxel-coated Mg-Zn-Y-Nd alloy intestinal stent and a barium sulfate-blended polyglycolic acid stent will be decomposed and excreted after the reconstructed intestine heals, thereby reducing the risk of inflammation. However, due to the high incidence of intestinal anastomotic stenosis caused by such stent treatments, their long-term efficacy is not ideal. Specifically, current biodegradable stents are generally hard or degrade slowly, so the risk of complications such as device displacement, tissue inflammation and obstruction is also high. Therefore, technical and operational breakthroughs are still needed in clinical treatment to address the limitations of existing methods and reduce the incidence of anastomotic leakage. From a clinical perspective, stent-based anastomosis is still the most promising solution, and the key lies in how to address the limitations and potential complications of such stents.

[0004] Most studies have shown that high molecular weight polytrimethylene carbonate (PTMC) is a flexible, biocompatible and biodegradable polymer with unique enzymatic degradability. In addition, the low level of hemolysis, coagulation and inflammatory response caused by the secondary neutral degradation products of PTMC shows advantages in the field of wound healing. Although the degradation process of PTMC is accompanied by shrinkage and deformation, it is still a good choice for biological tissue engineering scaffolds. Polyhydroxyalkanoate (PHA) is a rigid natural polymer with high mechanical strength produced by a variety of microorganisms, with good biocompatibility and the effect of promoting cell proliferation. Therefore, the performance combination of these two polymers can be obtained by physical blending to make up for the performance defects of a single polymer. In addition, as an intestinal anastomosis scaffold, it should also have cell affinity on the basis of reducing the tension of the anastomosis and isolating the intestinal contents, so as to accelerate the regeneration and healing of the anastomotic wound. It is well known that the extracellular matrix (ECM) serves as a surface for cell attachment and provides mechanical protection for cells. If fibroblasts are not attached or adhered to a suitable surface, they cannot proliferate and differentiate. To this end, electrospinning technology can be used to obtain nanofibers that are similar in structure and function to natural ECM, and due to their high free surface energy, they are very suitable for cell attachment, which is a necessary condition for cell proliferation and differentiation. In addition, the anastomotic stent obtained by electrospinning technology also has significant advantages such as high porosity, high surface area, and oxygen permeability, which enables this nanofiber platform to accelerate cell migration from the periphery of the wound to the center of the wound, thereby promoting anastomotic healing.

[0005] In addition, local application of antibiotics is an effective means to deal with the inflammatory response period 1 to 3 days after intestinal anastomosis. At the same time, considering that antibiotics and other drugs may affect the healing of the anastomotic proliferative period, it is hoped that this antibacterial function is only effective for a short period of time, and then it can be removed from the stent without affecting the subsequent functional application of the anastomotic stent. Summary of the invention

[0006] In order to solve the technical defects of the prior art, the present invention provides a double-layer structure flexible intestinal anastomosis stent with an antibacterial surface layer and a preparation method thereof.

[0007] The technical solution adopted by the present invention is: a double-layer structure flexible intestinal anastomosis stent with an antibacterial surface layer, wherein the intestinal anastomosis stent is composed of a PTMC / PHA nanofiber inner layer obtained by electrospinning technology after polytrimethylene carbonate (PTMC) and polyhydroxyalkanoate (PHA) are blended, and an antibacterial outer layer is obtained by adding gentamicin sulfate (Gs) to a blended solution of aldehyded hyaluronic acid (OHA) and polyvinyl alcohol (PVA) and continuously electrospinning to obtain a two-layer fiber structure.

[0008] In the PTMC / PHA nanofiber inner layer, the mass ratio of PTMC to PHA is 9:1-5:5.

[0009] The PTMC can be replaced by one or more of the following: PTMC-b-PEG-b-PTMC, P(TMC-c-CL), P(TMC-c-PDO), P(TMC-c-LA) and P(TMC-c-GA).

[0010] The PHA can be replaced by one or more of the following: PLA, PLGA5050, PBS.

[0011] The antibacterial outer layer fiber is prepared by continuous electrospinning of a mixed spinning solution of OHA, PVA and Gs on the basis of a PTMC / PHA fiber inner layer.

[0012] In the antibacterial surface layer of the PVA / OHA-Gs nanofiber, the mass ratio of PVA to OHA is 9:1-5:5.

[0013] The antibacterial surface layer of the PVA / OHA-Gs nanofiber contains 0.1-1.0% Gs.

[0014] The thickness of the PTMC / PHA nanofiber inner layer of the double-layer structure flexible anastomosis stent is 0.15-0.4 mm.

[0015] A method for preparing a double-layer flexible intestinal anastomosis stent with an antibacterial surface layer, characterized in that it comprises the following steps:

[0016] (1) Synthesis of PTMC: Using TMC monomers through catalytic ring-opening polymerization to synthesize polymer PTMC with a certain molecular weight;

[0017] (2) Electrospinning after blending PTMC and PHA: Weigh the prepared PTMC and PHA blend and dissolve them in hexafluoroisopropanol (HFIP) solvent to form a spinning solution with a solute concentration of 1.5-5 wt.%, and obtain the PTMC / PHA nanofiber inner layer structure by electrospinning;

[0018] (3) Synthesis of OHA and determination of hydroformylation degree: OHA was obtained by periodate oxidation of hyaluronic acid (HA) using sodium periodate (NaIO4) as an oxidant, and the hydroformylation degree of OHA was determined by 2,4-dinitrophenylhydrazine reagent (DNPH);

[0019] (4) Electrospinning after blending PVA, OHA and Gs: Weigh the prepared OHA and PVA and mix them to form a water-soluble spinning solution, then add a certain proportion of Gs into it. After it is completely dissolved, the PVA / OHA-Gs nanofiber antibacterial outer layer is obtained by continuous electrospinning on the basis of the prepared PTMC / PHA nanofiber inner layer.

[0020] The conditions for electrospinning in step (2) are: receiving distance 15-18 cm, injection speed 4-6 mL / h, shaft speed 600 RMP, voltage 18-22 KV.

[0021] The conditions for electrospinning in step (4) are: receiving distance 12-15 cm, injection speed 0.5-1 mL / h, shaft speed 600 RMP, voltage 16-20 KV.

[0022] The concentration of the water-soluble spinning solution in step (4) is 6-10 wt%.

[0023] The beneficial effects of the present invention are as follows: the present invention provides a double-layer structure flexible intestinal anastomosis stent with an antibacterial surface layer and a preparation method thereof, and adopts electrospinning technology to mix PTMC and PHA to form a stent inner layer with excellent mechanical properties, biodegradability, and conducive to cell migration and proliferation. At the same time, in order to cope with the risk of infection during the inflammatory period, adding antibiotics is an effective option. By loading Gs into PVA / OHA, its antibacterial effect can be exerted. Moreover, through the co-spinning of PVA and OHA, the fiber structure of this layer can remain in a gel state for a certain period of time after absorbing water, which makes Gs fully exert its antibacterial effect only in the early stage of anastomotic healing, avoiding the risk of infection at the anastomotic site, thereby indirectly promoting anastomotic healing. The excellent performance of the prepared flexible intestinal anastomosis stent was verified by physical, chemical and biological characterization of the stent inner layer, the antibacterial surface layer and the entire stent. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the preparation and application of the double-layer electrospun nanofibrous PTMC / PHA scaffold: (A) Assembly process, PVA / OHA-Gs layer with antibacterial function, and PTMC / PHA nanofibrous layer with ECM-like properties. (B) In an animal model, the intestinal anastomosis process and postoperative effects were compared between the PTMC / PHA double-layer scaffold implanted at the site of colorectal obstruction and the one without the scaffold implanted.

[0025] Figure 2Physical and chemical characterization of the double-layer electrospun PTMC / PHA scaffold and synthetic materials: (A) SEM image of the anastomotic scaffold; (B) FTIR and XRD spectra of PHA, PTMC and PTMC / PHA; (C) FTIR spectra of HA, OHA, PVA and PVA / OHA.

[0026] Figure 3 (A) Hydrophilicity and hydrophobicity contact angle test; (B) Mechanical properties of PTMC / PHA nanofibers at different PHA addition ratios; (C) PTMC, PHA, PTMC / PHA 20 PTMC / PHA 30 PTMC / PHA 40 (D) Trend of degradation rate at different time periods; (E) PTMC / PHA 30 Physical photos of nanofiber layers at different degradation times.

[0027] Figure 4 (A) Mechanical properties and (B) in vitro degradation rates of double-layer PTMC / PHA scaffolds of different thicknesses.

[0028] Figure 5 (A) SEM images of cell adhesion and proliferation on the surface of PTMC, PHA, and PTMC / PHA nanofiber layers at different times after cell inoculation; (B) MTT absorbance; (C) a local magnified image of cell adhesion and proliferation on the surface of PTMC / PHA fiber layers.

[0029] Figure 6 (A) Photographs showing the state changes of PVA / OHA with different mass ratios in methylene blue aqueous solution over time; (B) energy spectrum analysis of PVA / OHA and PVA / OHA-Gs.

[0030] Figure 7 (A) Effects of PVA / OHA-Gs layers containing different amounts of Gs on the inhibition zones of Escherichia coli and Staphylococcus aureus; (B) Bacterial colonies after PVA / OHA-Gs layers containing different amounts of Gs were in contact with Escherichia coli and Staphylococcus aureus; (C) Inhibition rate of PVA / OHA-Gs layers and (D) CCK-8 cytotoxicity test.

[0031] Figure 8 (A) Hemolysis rate test and (B) CCK-8 cytotoxicity test of different layer materials and the overall scaffold.

[0032] Fig. 9 Establishment of intestinal obstruction model: (A) The process of establishing the intestinal obstruction model; (B) Digital photos at different stages of intestinal obstruction, as well as H&E and Masson staining at different time points of obstruction.

[0033] Fig.10 (A) Stent implantation process; (B) abdominal adhesion score; (C) intestinal tissue photos; (D) anastomotic burst pressure at different time points after three different anastomosis schemes: Blank group, pure PTMC stent group and PTMC / PHA double-layer anastomosis stent group; (E) SEM images of the in vivo degradation of pure PTMC stent and PTMC / PHA double-layer anastomosis stent.

[0034] Fig.11 H&E staining and Masson staining were performed on the blank group, pure PTMC stent group and PTMC / PHA double-layer anastomotic stent group.

[0035] Fig.12 Immunological test analysis performed on the blank group, pure PTMC stent group and PTMC / PHA double-layer anastomosis stent group: (A) IL-6 fluorescence image and IL-6 fluorescence analysis; (B) CD31 fluorescence image and CD31 fluorescence analysis; (C) α-SMA fluorescence image and α-SMA fluorescence analysis. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Exploration of PTMC / PHA main scaffold

[0038] Synthesis of PTMC

[0039] We synthesized PTMC by ring-opening polymerization of TMC monomer. The details are as follows:

[0040] 1) In a vacuum glove box, weigh a certain amount of monomer TMC, add 1-5 wt.% of catalyst Sn(Oct)2 (dissolved in anhydrous toluene), add it to the reaction tube, put in a magnetic bar and seal the tube mouth with silicone grease, and finally seal the tube mouth with a sealing film to ensure that no oxygen and moisture enter;

[0041] 2) Take the reaction tube out of the glove box and place it in an oil bath to heat the reaction at 130-160°C for 48-60 h.

[0042] 3) After the reaction is completed, take out and add chloroform solvent, wait until it is completely dissolved, and purify the polymer solution with excess n-hexane, repeat 3 times. Place the purified precipitated polymer in a vacuum drying oven and dry it for 48 hours to obtain PTMC for standby use.

[0043] Exploration of blending ratio and thickness of PTMC and PHA

[0044] 1) Weigh a certain amount of prepared PTMC, add different amounts of PHA to make PTMC / PHA form a certain ratio (9 / 1, 8 / 2, 7 / 3, 6 / 4, 5 / 5), dissolve the above PTMC and PHA mixtures in different ratios in HFIP to form a spinning solution with a solute concentration of 3.5 wt.%, and finally perform electrospinning.

[0045] 2) After molding, the tensile properties were tested to explore the PTMC / PHA spinning scaffold with the best mechanical properties. At the same time, in order to explore its in vitro degradation performance, in vitro degradation experiments were performed on the scaffolds of each ratio, and a group of ratios with the best morphology during the degradation process and a degradation time of about three weeks were selected.

[0046] 3) Select the appropriate ratios mentioned above and perform the same tensile and degradation tests on different thicknesses under the same ratio conditions. Select the set of thicknesses with the best performance.

[0047] 4) Select the scaffold samples with the above thickness to conduct cell attachment experiments to determine the optimal blending ratio and optimal thickness of the main scaffold.

[0048] Exploration of antibacterial surface PVA / OHA-Gs

[0049] Synthesis of OHA

[0050] HA is an important component of the natural extracellular matrix and plays a vital role in various functions of cells and tissues. Using sodium periodate (NaIO4) as an oxidant, periodate oxidation of HA is a promising method for hydroxyl modification. The details are as follows:

[0051] 1) Weigh 1 g HA and dissolve it in 99 mL distilled water. Stir at 50°C for 3 h to allow it to dissolve naturally. Adjust the pH to 4 and shake it overnight at room temperature.

[0052] 2) Dissolve 0.42 g of NaIO4 in 10 mL of deionized water to prepare a 0.5 mol / L NaIO4 solution. Place in a syringe away from light.

[0053] 3) At room temperature and away from light, inject NaIO4 solution into the dissolved HA solution at a rate of 2.5 mL / h and stir for 6 hours in the dark. Then add 1 mL of ethylene glycol to remove unreacted sodium periodate.

[0054] 4) Place the solution in a 3000 Da dialysis bag and dialyze for 3 days, then freeze-dry and store.

[0055] Determination of OHA hydroformylation degree

[0056] The degree of hydroformylation of OHA was determined by using 2,4-dinitrophenylhydrazine (DNPH) reagent.

[0057] 1) First prepare the DNPH reagent solution: dissolve 40 mg of DNPH in 0.3 mL of concentrated sulfuric acid. Add 3 mL of ethanol to the slurry under continuous stirring at 25°C. Allow the mixture to react for 10 minutes to achieve homogenization. Then make up the volume to 10 mL with distilled water.

[0058] 2) Add 0.3% OHA to 10 mL of freshly prepared DNPH solution. Incubate the reaction mixture at 25°C for 1 hour and then centrifuge at 10,000 rpm for 10 minutes.

[0059] 3) Measure the unreacted ions in the supernatant at a wavelength of 357 nm using a UV spectrophotometer.

[0060] The absorbance of DNPH. The amount of aldehyde produced is calculated according to the following formula:

[0061]

[0062] Exploration of the spinning ratio of PVA / OHA-Gs 1) PVA was swelled with deionized water, then heated and dissolved at 90℃ for 2-3h to prepare a 10 wt. % PVA solution. 2) Then the prepared PVA and OHA were mixed to form a water-soluble spinning solution with different ratios (9 / 1, 8 / 2, 7 / 3, 6 / 4, 5 / 5). The spinning solutions with different ratios were used for spinning.

[0063] 3) After obtaining the antibacterial layers with different ratios, the swelling performance test and the degradation performance test are carried out to select the most suitable ratio of PVA / OHA spinning solution.

[0064] 4) Then add different contents of Gs (0.1%, 0.25%, 0.50%, 0.75%, 1.00%) to the spinning solution in appropriate proportions and shake at room temperature until a transparent solution is formed. Then spin and test the cytotoxicity and antibacterial properties of different contents. Select the proportion with good antibacterial properties and low cytotoxicity as the final antibacterial surface layer.

[0065] Physicochemical characterization of anastomotic stents

[0066] Fourier Transform Infrared Testing and X-Ray Diffraction

[0067] By using FTIR at 2 cm -1 The materials of the stent and the antibacterial surface were evaluated by 32 scans at a resolution of 100 nm. X-ray diffraction (CuKaradiation, 40 kV / 30 mA) was used for XRD phase analysis of the stent and the antibacterial surface.

[0068] Scanning electron microscopy and elemental analysis

[0069] 1) Place the sample in a vacuum freeze dryer for dehydration;

[0070] 2) The treated samples were fixed on the sample stage with conductive glue and loaded 60 s after gold spraying. A scanning electron microscope (SEM, SU8010, HITACHI, Japan) was used to observe the fiber structure of the stent and the antibacterial surface layer, as well as the side structure of the overall anastomotic stent.

[0071] 3) In order to verify the addition of antibacterial components to the antibacterial surface, elemental analysis was performed on the antibacterial surface after gold spraying.

[0072] Contact angle test

[0073] Determination of the water contact angle of the scaffold by the sessile drop method The water contact angle of the scaffolds with different proportions was measured using an optical video contact angle meter. First, the scaffold test surface was placed flat at the bottom of the pipette gun, and 5 μL of deionized water was dropped onto the sample surface through the software, the drop image was recorded, and the contact angle was measured using the Digimizer software. For each sample, the process was repeated three times (n=3).

[0074] Mechanical properties test

[0075] The tensile strength test was performed using an electronic universal material testing machine (5944, Instron, USA) to study the mechanical properties of the stent. Different stent samples of the same length and thickness were cut and fixed at both ends of the tensile mold of the testing machine. After the displacement and force were adjusted to zero, the test was started. The Young's modulus, tensile strength, and elongation at break of the stent and intestine measured by the stress-strain curve were recorded. Each experiment was repeated for 3 samples (n=3).

[0076] In vitro biodegradation evaluation

[0077] The required scaffold diameter is 1 cm, which is weighed in advance and recorded as W0. The scaffold is placed in 10 mL of simulated intestinal fluid (USP protocol) and shaken in a shaker at 37°C to simulate intestinal peristalsis. The samples (N=3) are then taken out within the specified time (3, 5, 7, 14, 21 days). The surface of the removed samples is cleaned with deionized water and dried at room temperature to a constant weight. Then it is weighed and recorded as W t The weight loss rate of the sample was calculated using the following formula:

[0078]

[0079] In vitro biological evaluation

[0080] Blood compatibility

[0081] Blood compatibility experiments were performed as reported in the literature. First, 20 mg of the stent sample was added to 9 mL of normal saline and incubated at 37°C for 24 h to obtain the sample extract. Then, fresh anticoagulated blood (200 μL) was added to the extract (1 mL) and mixed thoroughly. After incubation (37°C) for 1 h, the mixture was centrifuged (3000 rpm, 10 min). Finally, the absorbance of the supernatant was measured using an automatic microplate reader (540 nm). The negative control was normal saline (NS), and the positive control was deionized water (DW).

[0082]

[0083] Among them, ODS, ODN, and ODP represent the absorbance of scaffold sample, NS, and DW at 545 nm, respectively.

[0084] Cell-related experiments

[0085] Isolation and culture of fibroblasts

[0086] 1) Maintain L929 fibroblasts in DMEM medium at 37°C and 5% CO2, and replace the medium every 1-2 days.

[0087] 2) When the cells have grown to about 90% of their density, use trypsin to digest them. After the cells are detached from the cell wall, add DMEM medium immediately to terminate the digestion.

[0088] 3) Centrifuge the cell suspension, discard the supernatant, add an appropriate amount of DMEM culture medium and mix well. Pipette 10 μL of cell culture medium into a cell counting plate for counting, and make the cell concentration 1×10 5 cells / mL.

[0089] CCK-8 test

[0090] 1) After all scaffold samples were sterilized by ultraviolet light for 4 h, scaffold solution samples (concentration of 10 mg / mL) were prepared using DMEM medium;

[0091] 2) Add 100 μL of cell suspension (concentration of 1×105 cells / mL) to a 96-well plate and incubate at 37°C and 5% CO2 for 24 h; replace the culture medium in the well plate with 100 μL of sample solution and continue incubating for 24 h. Add 10 μL of CCK-8 reagent to each 96-well plate and continue incubating for 2 h.

[0092] 3) Use an ELISA reader to measure the absorbance of the samples in the well plate at 450 nm and calculate the cytotoxicity. The calculation formula is as follows:

[0093]

[0094] Among them, A S is the absorbance of the cell suspension that the scaffold sample contacts, A B and A C are the absorbance of the control group and the blank group, respectively.

[0095] Cell proliferation assay (MTT method)

[0096] 1) Use PBS solution containing MTT (tetrazolium bromide, Sigma Aldrich) (concentration: 5 mg / mL). Add MTT solution (40 μL) to the seeded scaffold and incubate at 37°C for 4 h.

[0097] 2) Remove the MTT solution and add 200 μL of extraction solution (89% isopropanol, 10% Triton-X, 1% HCl, 0.37%) to the wells. Stir for 10 minutes in a stirrer (150 rpm) and incubate with the extraction solution for 2 hours at room temperature without light to dissolve the blue-purple crystalline formazan crystals.

[0098] 3) After homogenization, transfer 200 μL of the supernatant from each well to a 96-well plate and measure the absorbance at 570 nm.

[0099] Cell morphology

[0100] 1) To evaluate cell morphology, we observed by SEM. The cells were dehydrated and fixed with 2.5% glutaraldehyde for 4 hours at room temperature;

[0101] 2) The scaffolds were then washed three times with PBS and distilled water, and dehydrated in different concentration gradients of ethanol (25%, 50%, 75%, 95% and 100%). Each dehydration lasted for 10 minutes;

[0102] 3) Finally, after drying in a fume hood, the cell morphology was observed by scanning electron microscopy.

[0103] Antibacterial study

[0104] 1) In order to determine the appropriate drug loading of the outermost layer of Gs, we prepared PVA / OHA-Gs spinning scaffold samples containing different amounts of Gs. Staphylococcus aureus (ATCC29213) and Escherichia coli (ATCC8739) were used as two different Gram-positive and Gram-negative model microorganisms to determine the inhibition zone and inhibition rate of the materials.

[0105] 2) First, cut the prepared stent sample into a circular sample with a diameter of 8 mm, and then perform UV sterilization. Take 100 μL of 1×10 8 Smear the CFU / mL bacterial solution on the nutrient agar plate, place the circular sample in the center of the coated plate, put it in the incubator, culture it overnight, and observe the size of the inhibition zone the next day.

[0106] 3) Then weigh 5 mg of scaffold samples with different Gs contents and soak them in a 1×10 6 CFU / mL in 1 mL of bacterial solution, incubate at 37℃ for 2 h, dilute the colony suspension to the counting range, spread it on the nutrient agar plate, and put it in the mold incubator. After culturing overnight, colonies are formed on the agar plate. After counting the number of colonies, the inhibition rate is calculated respectively.

[0107] In vitro biological evaluation

[0108] Establishment of mechanical intestinal obstruction model in rabbits

[0109] According to the references, we improved the rabbit mechanical intestinal obstruction model and established this model to evaluate the effect of the anastomotic stent on the repair and healing of the anastomosis during anastomosis after intestinal obstruction. The specific operation is as follows:

[0110] 1) 18 rabbits were randomly divided into 6 experimental groups (3 rabbits in each group). Before the experiment, the rabbits should be fasted for 24 hours and allowed to drink water freely to empty the intestinal contents and provide a clear view for the subsequent intestinal surgery.

[0111] 2) Induce anesthesia in the rabbit with Su Mian Xin. After the effect is achieved, administer isoflurane and oxygen mask anesthesia. After the rabbit is deeply anesthetized, perform laparotomy.

[0112] 3) A soft rubber tube was placed in the non-vascular area of ​​the mesentery 5 cm distal to the anus to ligate the intestine. The rabbits were obstructed for different times (6h, 12h, 18h, 24h, 30h, 36h). The rabbits in the sham operation group underwent simulated intestinal surgery without locking ligation.

[0113] 4) Obtain the rabbit's obstruction status at the most appropriate time point based on H&E and Masson analysis results.

[0114] Application evaluation experiment of anastomotic stent implantation in animal model

[0115] 1) The rabbits after the above obstruction experiment were fixed with a wooden fixator and anesthetized by intramuscular injection of 0.1-0.2 mL / kg of sulfanilamide. After the effect took effect, isoflurane and oxygen were given through mask anesthesia.

[0116] 2) After opening the abdominal cavity, pull the intestinal tract to be operated on out of the wound, protect and isolate it with gauze soaked in saline, select the target intestinal tract, gently squeeze the chyle in the intestinal segment to both sides, clamp a pair of intestinal forceps on both sides, and tie the blood vessels at the target intestinal segment;

[0117] 3) Make an incision at the part of the contralateral mesentery where there are fewer blood vessels. After the incision, the aseptic surgery is transferred to the aseptic surgery. Hold the intestinal clamp handle to bring the two ends of the intestine together. Pay attention to aligning the two intestinal cavities without twisting them. Separate them with saline gauze pads. Use No. 1 silk thread to suture the muscle layer at the mesentery and its contralateral edge, about 0.5 cm away from the end of the intestinal tube. Do not tie a knot for the time being. Clamp the end with a vascular clamp for positioning and traction;

[0118] 4) The traditional surgery blank group sutured the anastomosis site with silk thread in an end-to-end suture manner;

[0119] 5) The control group implanted with PTMC stents and the experimental group implanted with experimental stents continued with the following operations. The stent was embedded in the intestinal cavity, and only four diagonal fixation sutures were made with No. 1 silk thread. After that, the anterior and posterior walls of the anastomosis were sutured with No. 1 silk thread in an interrupted full-thickness manner (6 stitches were sutured at the anastomosis site);

[0120] 6) After suturing, remove the intestinal clamp, replace the gauze and instruments used for anastomosis, rinse the gloves with saline, and wipe them dry with iodine cotton balls. Gently squeeze the intestinal tubes at both ends with your hands to observe whether there is leakage at the anastomosis, and then rinse with saline.

[0121] Abdominal adhesion score

[0122] At selected time points (3, 5, 7, and 14 days), the rabbits underwent another laparotomy after surgery, and the adhesions in the abdominal cavity were observed and graded to obtain quantitative results.

[0123] Anastomotic burst pressure

[0124] The bursting pressure of anastomotic tissue is an important mechanical index for detecting the healing strength of anastomotic stoma. It reflects the pressure that the intestine can withstand and is generally used to detect the healing strength of anastomotic stoma. The bursting pressure test was performed on the anastomotic intestinal segments at different recovery time points after surgery, using an in vitro pressure measurement method. Specifically, the intestinal tube of about 5 cm around the anastomosis and the intestinal contents were rinsed clean with normal saline. One end of the intestinal tube was connected to a pressure gauge (YB-150A precision pressure gauge) and fixed with silk thread, and the other end was also tied to the peristaltic pump with silk thread so that the intestinal tube and the pressure gauge were at the same level. A peristaltic pump was used to uniformly inject methylene blue dilution (0.16 mg / mL) into the intestinal tube at a speed of 10 mL / min, and the reading on the pressure gauge when blue liquid overflowed from the anastomosis (or the pressure suddenly dropped) was recorded as the bursting pressure value of the anastomosis.

[0125] Histological analysis

[0126] H&E staining

[0127] 1) On the 1st, 3rd, 5th, 7th and 14th day after implantation, the anastomotic tissue was cut open and fixed with 4% paraformaldehyde solution. After dehydration with different concentrations of ethanol, the tissue was routinely embedded in paraffin and sliced ​​into paraffin blocks with a thickness of 4 μm;

[0128] 2) Dehydration of paraffin sections: Place the paraffin sections in xylene, anhydrous ethanol, and 75% alcohol, and finally wash with deionized water;

[0129] 3) Hematoxylin staining: Stain the sections with hematoxylin stain for 3-5 min, rinse with deionized water, differentiate with differentiation solution, rinse again with deionized water, then blue with bluing solution, and finally rinse with running water;

[0130] 4) Eosin staining: Dehydrate the sections in 85% and 95% graded alcohol for 5 min each, and then stain them in eosin staining solution for 5 min.

[0131] 5) Dehydrate, seal and examine under a microscope.

[0132] Masson staining

[0133] 1) Dehydrate in the same way, then soak the sections in Masson A solution overnight and wash with tap water;

[0134] 2) Slices were immersed in a dye solution of Masson B and Masson C in equal proportions for 1 min, rinsed with deionized water, differentiated with 1% hydrochloric acid alcohol, rinsed with deionized water, immersed in Masson D for 6 min, rinsed with deionized water, and immersed in Masson E for 1 min;

[0135] 3) Without washing, drain slightly and directly put into Masson F solution for 2-30 seconds, rinse and differentiate the slices with 1% glacial acetic acid, and dehydrate with two cylinders of anhydrous ethanol;

[0136] 4) Seal the slides and examine them under a microscope.

[0137] Immunofluorescence staining

[0138] 1) Wash the tissue slices with TBS (Tris buffered saline) for 5 minutes × 2 to facilitate antigen-antibody binding;

[0139] 2) Blocking solution (10% serum + 1% BSA) + 0.3% triton-100* at room temperature for 2 hours;

[0140] 3) Incubate with primary antibodies (CD31, α-SMA, IL-6) at 4°C overnight, with a concentration of approximately 1 μg / mL;

[0141] 4) Wash the tissue slices with TBS solution for 5 minutes × 3;

[0142] 5) Incubate with secondary antibody at room temperature for two hours or at 4°C overnight;

[0143] 6) Wash the tissue slices on a shaker in TBS solution for 5 minutes x 3, stick the tissue slices on a glass slide in a dark room, and dry them at room temperature. It is best to treat the glass slide with formaldehyde gelatin to prevent it from sticking and falling off;

[0144] 7) Seal the slides with 90% glycerol, paying attention to air bubbles. Prepare 90% glycerol in advance, use a 20 mL glass vial or test tube, add glycerol and PBS (or TBS OR saline), mix well, and let it stand to eliminate bubbles.

[0145] 8) Fluorescence observation: Place the slide under an upright fluorescence microscope for observation.

[0146] Statistical analysis

[0147] The experimental data are expressed as mean ± standard deviation (SD) (n = 3). Statistical analysis was performed using one-way ANOVA with Graph Pad Prism, and p value < 0.05 was considered significant.

[0148] Results Analysis

[0149] Preparation of anastomotic stent and its antibacterial surface

[0150] According to our previous description, the scaffold is prepared by electrospinning layer by layer from the inside to the outside. PTMC and PHA are placed in HFIP and prepared into a spinning solution with a concentration of 3.5 wt.%. Spinning is performed in an appropriate proportion to obtain the PTMC / PHA fiber inner layer of the scaffold. Then PVA is mixed with homemade OHA to prepare a water-soluble spinning solution, and Gs is added. On the basis of the inner layer, a PVA / OHA-Gs surface layer with antibacterial properties is prepared by continuous electrospinning ( Figure 1 A). The outer layer PVA / OHA-Gs mainly exerts antibacterial effects in the early stage of implantation, while the inner layer PTMC / PHA mainly plays a "bridge" role in cell migration. The prepared anastomotic stent was implanted into a rabbit mechanical intestinal obstruction model to verify its effect on the healing of the rabbit intestinal anastomosis, and compared with the traditional manual suture method ( Figure 1 B). The anastomotic recovery effect of the experimental group implanted with our prepared anastomotic stent was better than that of the control group sutured with traditional silk thread, and the chance of leakage at the anastomotic site was lower.

[0151] FTIR and XRD of PTMC / PHA inner layer

[0152] We tested the infrared spectra of PHA, PTMC and PTMC / PHA spun films respectively ( Figure 2 Ba). For PTMC fiber membrane, -CH2- can be observed at 2970 cm -1 and 2909 cm -1 At 1735cm, C=O -1 and -O- at 1218 cm -1 For PHA films, at 1720 cm -1 There is a carbonyl absorption peak at 1276 cm -1 , 1180 cm -1 and 1057cm -1 There is an ester absorption peak at . For the PTMC / PHA fiber membrane, all characteristic peaks belonging to PTMC and PHA can be found, and the position of the peaks does not change significantly. Therefore, it can be inferred that there is almost no mutual influence between PTMC and PHA molecules in the composite material, and the material properties of both can be retained.

[0153] XRD can intuitively distinguish between crystalline and amorphous ( Figure 2Bb). For the pure PTMC scaffold, the convex diffraction peaks in the spectrum indicate that the scaffold is non-crystalline. However, due to the crystalline nature of the polymer chain, the 2θ peaks of the pure PHA film are at 13.46, 15.21, 16.81, 20.01, 25.38, and 26.89, respectively. Most of the peaks of PHA can be clearly observed in the diffraction peaks of the PTMC / PHA scaffold, so the blended scaffold does not change the crystallinity of PHA, thereby maintaining good mechanical properties.

[0154] Physical properties of PTMC / PHA inner layer

[0155] In order to explore the optimal ratio of PTMC and PHA and obtain the best hydrophilicity for cell adhesion, the optimal contact angle suitable for cell adhesion was obtained by exploring different ratios ( Figure 3 A). The contact angle of the PTMC / PHA inner layer decreases with the increase of PHA content, and the hydrophilicity increases. When the optimal ratio of PTMC and PHA is about 7 / 3, the contact angle is about 65°, which is consistent with the characteristics of mammalian cells that prefer to adhere and proliferate with moderate hydrophilicity, that is, the contact angle is about 50-70°. At the same time, the scaffold should have appropriate mechanical properties ( Figure 3 B). It can be observed that as the addition ratio of PHA increases, the tensile elongation of the PTMC / PHA inner layer gradually decreases and the Young's modulus gradually increases. When the PTMC / PHA ratio is 7 / 3, its Young's modulus is between 7-10 MPa and the elongation is about 400%, which makes it have good flexibility and certain rigidity, that is, it has the performance advantages of both materials. Under the condition of 7 / 3, we also explored the mechanical properties of different thicknesses and found that when the thickness is about 0.2 mm, the mechanical properties of the PTMC / PHA inner layer are better, and its mechanical strength and tensile elongation have reached the optimal effect ( Figure 4 A). Therefore, we selected the PTMC / PHA inner layer with a thickness of 0.2 mm and a ratio of 7 / 3 as the main layer structure of our stent.

[0156] In vitro degradation of PTMC / PHA

[0157] Based on the above experiments, we found that the ratio of PTMC / PHA between 8 / 2-6 / 4 had better performance, so we further explored their in vitro degradation. Figure 3E) It can be found that when the PTMC / PHA ratio is 7 / 3, the macroscopic structure of the scaffold can be maintained in simulated intestinal fluid in vitro for about two weeks. After that, as time goes on, it gradually breaks apart in about three weeks. The broken layer structure has almost no mechanical properties and causes almost no damage to the real intestine. In terms of microscopic morphology, when the PTMC / PHA ratio is 7 / 3, as the degradation time increases, its randomly oriented fibers can still maintain a good morphology for about 1 week, which provides a good spatial framework for cell attachment during the intestinal healing period. And some studies have also shown that such randomly oriented fibers are more conducive to cell proliferation and adhesion. At the same time, we explored its weightless degradation rate in vitro ( Figure 3 D) We found that the degradation rate of the 7 / 3 PTMC / PHA inner layer structure can reach 60-70% in 21 days. Because the environment in the intestine is relatively complex, it will accelerate the degradation of the stent. Therefore, in order to prevent the stent from degrading during the intestinal healing period, we finally selected the PTMC to PHA ratio of 7 / 3 for the next exploration.

[0158] SEM image of cells attached to the inner layer of PTMC / PHA

[0159] To verify the properties of PTMC / PHA in promoting cell adhesion and proliferation, we compared the SEM images of cell adhesion and proliferation of simple PTMC, PHA, and our prepared PTMC / PHA inner layer at different time periods after cell inoculation ( Figure 5 A). The results showed that as the culture time increased, the number of scaffolds attached to the hybrid scaffold was greater than that of the scaffolds prepared from the other two single materials. Due to its filamentous structure, the pure PTMC scaffold material dissolves quickly into a sheet structure, which is not conducive to cell proliferation and adhesion. Although the pure PHA scaffold has cell adhesion and proliferation effects, its cell adhesion and proliferation advantages are not obvious due to its regular fiber structure. At the same time, we conducted an absorbance test on cell proliferation ( Figure 5 B). Compared with the cell proliferation in the control group and the blank culture dish, it was found that the inner layer of the PTMC / PHA scaffold had the least effect on cell proliferation, that is, more cells appeared on its surface. By enlarging the local area of ​​the PTMC / PHA inner layer ( Figure 5 C), it can be found that cells mainly adhere to the part where the fibers are interlaced. In addition, because the large and small fibers in the inner layer structure of PTMC / PHA support each other, the fibers can be maintained for a long time, indirectly promoting the adhesion and proliferation of cells. Therefore, we successfully completed the preparation of the anastomotic scaffold part based on PTMC / PHA.

[0160] Exploration of antibacterial surface materials

[0161] With the help of FTIR ( Figure 2Ca), the formation of aldehyde groups on OHA has been confirmed. When looking at the spectrum of HA alone, the -1 、2906 cm -1 、1617 cm -1 、1039 cm -1 There are absorption peaks around 1726 cm -1 A new peak is formed at 357 nm, which is the characteristic absorption peak of the aldehyde group. At the same time, the absorbance of DNPH with different standard concentrations at 357 nm was measured by UV spectrophotometer, and its standard curve was determined to be y=0.0842x+0.0212, and the degree of hydroformylation of OHA was calculated to be about 26%.

[0162] After obtaining the modified OHA, we observed its changes after adding PVA by FTIR ( Figure 2 Cb). The spectrum shows at 2945 cm -1 、1734 cm -1 and 1250 cm -1 are characteristic peaks of PVA, which are related to alkyl, acetyl and -CO- groups respectively. The infrared spectrum of PVA / OHA after spinning clearly shows that the characteristic peaks of both groups appear, that is, after the co-spinning of PVA and OHA, the absorption peaks of their own groups do not change. Moreover, we found that when the ratio of OHA to PVA is 6 / 4, the outer layer structure formed by spinning can persist in the methylene blue aqueous solution for about 48 h ( Figure 6 A). This allows it to remain in the intestinal wall for a certain period of time, allowing Gs to exert a rapid antibacterial effect. And when PVA / OHA is dissolved in the intestinal wall, Gs will also be lost, which prevents Gs from existing in the intestinal wall for a long time, and also reduces the damage caused by antibiotics to the intestinal flora, protects the intestinal flora microenvironment, and provides a strong guarantee for promoting intestinal healing. Finally, elemental analysis can verify the addition of Gs to the stent and its distribution range ( Figure 6 B), it can be clearly observed that the S element is evenly distributed on the fiber filaments of the inner layer structure. This provides a good condition for the uniform release of Gs. In addition, the increase in the content and proportion of the S element after adding Gs can be detected by elemental analysis, thereby verifying the percentage of Gs added.

[0163] Study on Gs content in antibacterial surface layer

[0164] In order to verify the addition of different amounts of Gs, the addition of different amounts of Gs was explored under the condition of PVA / OHA ratio of 6 / 4. As the Gs content increased, the inhibition zone against Escherichia coli and Staphylococcus aureus gradually increased ( Figure 7 A), the antibacterial rate also gradually increased ( Figure 7B). When the Gs content is 0.5%, the inhibition rate against Escherichia coli and Staphylococcus aureus reaches more than 90% ( Figure 7 C). In addition, we conducted cytotoxicity tests on the antibacterial surfaces with different Gs contents ( Figure 7 D), it was found that the cytotoxicity of Gs to cells increased with the increase of its content. Based on the results of the inhibition zone, inhibition rate and cytotoxicity test, it was analyzed that when the Gs content was 0.5%, the antibacterial surface layer could effectively play an antibacterial role while causing minimal damage to cells. Therefore, the electrospun fiber layer with a PVA / OHA ratio of 6 / 4 and a Gs content of 0.5% was selected as the antibacterial surface layer.

[0165] SEM observation

[0166] Based on the above research, we obtained the final intestinal anastomosis scaffold and characterized it for final verification. First, by observing the SEM image ( Figure 2 A), you can see the side structure of the scaffold: the PTMC / PHA inner layer structure is distributed with two kinds of fibers of uniform thickness, and the fine fibers are scattered between the thick fibers, which further strengthens the stability of the overall fiber structure and provides an ECM structure similar to the extracellular matrix for cell adhesion and proliferation; one side of the antibacterial surface layer is distributed with a single fine fiber with small porosity and dense structure, which provides a good release basis for its antibacterial property.

[0167] Degradation rate and mechanical properties

[0168] At the same time, we explored the degradation of the whole scaffold. Based on the PTMC / PHA inner layer with thickness of 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, and 0.5 mm, we electrospun an antibacterial surface layer of the same thickness for degradation observation ( Figure 4 B). It was found that the fiber filaments of the 0.2 mm thick anastomosis stent gradually broke within 21 days, and the in vitro degradation rate analysis found that its degradation rate within 21 days reached about 70%, which is suitable for implantation in the intestine of animals. At the same time, the mechanical properties of the stent of this thickness were compared with those of the intestine, and we found that its Young's modulus and tensile elongation were better than those of the intestine itself.

[0169] In vitro biological evaluation

[0170] At the same time, in order to verify its biocompatibility, we conducted hemolysis test and cytotoxicity test ( Figure 8A, 8B) It was found that the hemolysis rates of the PTMC / PHA inner layer, the PVA / OHA-Gs antibacterial surface layer, and the entire intestinal anastomosis stent were far below 5%, and there was no toxic damage to the cells after co-incubation. Therefore, it has good biocompatibility and is suitable for implantation in animals. Then, the bacteria were imaged in vivo under a laser confocal microscope, and it was observed that the intestinal anastomosis stent with the addition of Gs had an effective bactericidal effect on Escherichia coli and Staphylococcus aureus. On the contrary, the anastomosis stent without the addition of Gs had no bactericidal effect.

[0171] Analysis of mechanical intestinal obstruction model in rabbits

[0172] The rabbit intestinal obstruction experimental model was designed, and the rabbit mechanical intestinal obstruction model was established by extraintestinal compression. The infusion hose widely used in clinical practice was used as an intestinal locking clamp ( Fig. 9 A). Since the incidence of colorectal cancer is relatively high, we chose the colorectal area as a mechanical obstruction model. After opening the abdomen, a soft infusion tube was used to form a uniform ring obstruction in the non-vascular area of ​​the mesentery 5 cm distal to the anus. Photos were taken to record the intestinal conditions at different time points after the obstruction ( Fig. 9 B). It can be observed that within 12 hours of intestinal clamping, a small amount of feces can be seen moving to the obstruction site, and no intestinal dilatation occurs. As time goes on, gas and feces accumulate in the intestine that has been clamped for 18 hours, causing intestinal dilatation and obstruction. As time goes on, gas and feces gradually increase, and the intestine continues to dilate, resulting in severe obstruction after 24 hours. Subsequently, the obstruction continues to worsen, causing intestinal ischemia, which is irreversible. At the same time, we combined the H&E and Masson staining analysis of intestinal obstruction pathology ( Fig. 9 B). Through H&E observation, the pathology within 12 hours of intestinal clamping did not differ significantly from that of normal intestines. As the obstruction time prolonged, the thickness of the intestinal mucosal layer gradually decreased and fell off at 30 hours, eventually leading to severe damage to the entire mucosal layer. After that, the integrity of the intestinal epithelium was completely lost, and the intestinal mechanical barrier was severely damaged. Masson staining also showed that its collagen fibers gradually decreased as the obstruction worsened, and the morphology was gradually severely damaged. At the same time, blood vessels and vascular systems gradually expanded, eventually leading to rupture, causing congestion and edema. Too mild or too severe is not conducive to the conduct of our experiment, so we selected the time point of the obstruction model for the next experiment when the intestine was clamped for 18 hours (the time point when the obstruction began).

[0173] Matching experiment

[0174] The rabbits were relieved of obstruction after 18 hours of obstruction, and then the wound was cut open with surgical scissors to empty the contents. A blank group (traditional manual silk suture group), a control group (implanted with pure PTMC stent) and an experimental group (implanted with the prepared double-layer flexible stent with antibacterial surface) were set up. The blank group was sutured by conventional surgical suture, and the control group and the experimental group were implanted with stents according to our schematic diagram ( Fig.10 A). During the postoperative recovery process, we opened the abdomens of the three groups to observe their internal conditions. It was found that some contents in the intestine of the blank group were attached to the anastomosis, and there was a possibility of overflow on the outside. Observation of the control group and the experimental group found that the stent in the control group collapsed due to shrinkage, causing secondary obstruction. At the same time, it could not fit closely with the intestine, resulting in the accumulation of intestinal contents at the stent and the anastomosis, causing extreme expansion of the upper intestine, incomplete healing, and blood congestion. The stent in the experimental group fit tightly with the intestine, the intestinal anastomosis was restored intact, and no other pathological changes observable to the naked eye, such as tissue edema and hypertrophy, occurred, and the overall structure of the stent did not shrink, which fully demonstrated that the stent we prepared had good biocompatibility and protective effects on the healing process of the intestinal anastomosis, which provided a guarantee for indirectly promoting the healing of the anastomotic wound.

[0175] Relevant characterization of the matching experiment

[0176] Abdominal adhesion score

[0177] When the abdominal cavity is stimulated or damaged and infected, the local fibrin gelatinous liquid is converted into fibrin coagulation, which covers the wound mucosal surface and plays a role in repair and protection. However, the highly adhesive fibrin can cause abdominal adhesion and affect the normal physiological activity of the intestine. Therefore, we use the anastomotic adhesion score to determine the impact of stent implantation on the normal physiological activity of the intestine within 1 week ( Fig.10 B). We found that the adhesion scores caused by fecal leakage in the blank group and the control group were significantly higher than those in the experimental group. In the control group, the pure PTMC scaffold was severely deformed, causing the body to have severe adhesions in order to protect the intestine. In contrast, in the experimental group, we found that the scaffold we prepared had little effect on the intestine, and the adhesion level was also the lowest. This played a positive role in promoting intestinal healing.

[0178] Anastomotic burst pressure

[0179] The bursting pressure of the tissue anastomosis after stent implantation can effectively reflect the firmness of the healing of the anastomosis after a period of time. This mechanical index can quantitatively reveal the tension that the anastomosis can withstand ( Fig.10D). It can be clearly observed that the anastomotic bursting pressure of the experimental group gradually recovered to the level before anastomosis as the healing time prolonged, while the bursting pressure of the blank group and the control group was lower than the normal intestinal bursting pressure due to incomplete wound healing. This further illustrates that our stent protects the healing of the anastomotic site and is conducive to the smooth recovery of the intestine to a normal state.

[0180] Degradation of stents in vivo

[0181] The morphological changes after stent implantation can better explain the morphological maintenance ability of the double-layer stents we prepared ( Fig.10 E). Therefore, its structural stability provides a good cell-like matrix platform for cell adhesion and proliferation at the anastomosis. It can be found that the fiber filaments of the control group were quickly destroyed and dissolved about 3 days after implantation in the body, causing its structure to collapse. However, the stent of the experimental group can still maintain the interlaced support of fibers of different thicknesses in the intestine for a week, proving the good mechanical properties and structural stability of the experimental stent.

[0182] Organization physical map observation

[0183] The intestinal recovery of rabbits in each group was observed and photographed on the 1st, 3rd, 5th, 7th and 14th day after stent implantation. Fig.10 C). It can be observed that under the same suturing method and number of stitches, the wound of the rabbits in the blank group was infected at the wound anastomosis due to contact with intestinal contents, resulting in the inability of the wound to heal smoothly. The pure PTMC scaffold in the control group contracted, and the contents contacted the wound, resulting in the inability of the anastomosis to heal. The scaffold in the intestine of the rabbits in the experimental group played a barrier role in intestinal healing, and at the same time had a certain antibacterial effect in the early stage of intestinal healing. The anastomosis healed within 7 days and no leakage was found. It was observed that the tissue had significant progress in wound healing (i.e., from incomplete healing at the beginning to complete recovery of the wound at the later stage). This once again illustrates the advantages of the double-layer scaffold we prepared in promoting intestinal healing.

[0184] H&E staining

[0185] To further illustrate the healing of the intestine, we further verified the healing of the intestine through H&E pathological sections ( Fig.11A). Through the observation of H&E in the three groups, we found that although the intestinal tissues of the blank group and the control group showed a general healing trend, careful observation revealed that the infiltration of inflammatory cells was throughout the entire healing process. The continuous inflammatory damage caused obvious obstacles to their healing, causing excessive or insufficient tissue proliferation, and the mucosa was never able to cover the anastomosis. In contrast, in the experimental group, we can find that its inflammatory infiltration began to decrease around the 5th day, and at the same time, the anastomosis gradually healed, the damaged muscle layer was gradually repaired, the leakage was reduced, and the mucosa was covered. On the 7th day, the mucosal apposition was nearly completed, the degree of inflammatory infiltration was significantly reduced, and the healing was initially completed in about two weeks.

[0186] Masson staining

[0187] Combined with Masson staining ( Fig.11 B), we can also observe that: the formation of collagen fibers in the blank group was significantly delayed, and significant collagen formation only began around the fifth day, which further prolonged its healing cycle; while the collagen fibers in the control group were generated in the early stage, but the collagen was greatly reduced on the fifth day, which may be due to the shrinkage and deformation of the pure PTMC scaffold, which made the tissue healing environment worse and hindered the healing process; the collagen fiber proliferation in the experimental group gradually increased, and the large-scale generation of collagen fibers after two weeks provided strong evidence for strengthening the strength of the anastomotic site. In summary, although the trend of the blank group was similar to that of the experimental group, the degree of healing was not as good as that of the experimental group in the same cycle. The healing of the control group was more obviously inferior. The mucosa was not apposed, and the inflammatory infiltration was obvious throughout the cycle, and the collagen fiber formation was insufficient, which led to the unsatisfactory strength of the anastomotic site. Therefore, the scaffold prepared by us has a good protective effect and a positive promoting effect on the healing of the anastomosis.

[0188] Immunofluorescence

[0189] We further analyzed the tissue at the anastomotic site by immunofluorescence for IL-6, CD31, and α-SMA. IL-6 immunofluorescence was performed to characterize the level of infection-induced inflammation during wound healing ( Fig.12A). We can clearly observe that the expression of IL-6 in the experimental group showed a significant downward trend as the healing time went by, and the expression of IL-6 tended to disappear around the 7th day, indicating that the inflammation basically disappeared during the healing process. Although the degree of inflammation in the blank group and the experimental group was generally similar, the inflammatory expression in the later stage was higher, which may be due to the increase in the amount of feces adhering to the anastomosis site in the later stage, which made the inflammation in the later stage disappear more slowly. The overall inflammatory expression in the control group was significantly too high, which may be due to the shrinkage of the stent leading to obstruction, so that feces and the like came into contact with the anastomosis, thereby significantly increasing the expression of IL-6. At the same time, vascularization is also one of the important indicators for measuring wound healing and is the most important process in tissue repair. CD31 immunofluorescence staining can observe the angiogenesis during tissue treatment ( Fig.12 B). The expression of CD31 in the experimental group reached a peak at about 3 days, and then gradually decreased slowly after 5 days. This is because in the early stage of healing, the scaffold in the experimental group created a relatively clean healing environment for it, the body quickly started repair, a large number of new blood vessels were generated, and the expression increased accordingly. In the process of gradual recovery of healing, the new blood vessels gradually decreased. The initial angiogenesis in the blank group was worse than that in the experimental group. This may be because the initial recovery of the blank group was affected by intestinal feces. The obvious lack of CD31 expression in the control group once again illustrates the damage to healing caused by the shrinkage of the scaffold. α-SMA is the most common marker of myofibroblasts in tissues and can be used to identify myofibroblasts. Myofibroblasts are involved in the contraction of the wound surface and the process of tissue fibrosis. Therefore, α-SMA plays an important role in the fibrosis of tissue healing ( Fig.12 C). We can find that the fibrosis level of the experimental group reached a peak on the 5th day and then decreased. It can be seen that the fibrosis showed a trend of first increasing and then decreasing, which prevented excessive fibrosis and adhesion formation while the tissue healed in the early stage. The initial fibrosis level of the blank group and the control group was higher than that of the experimental group, which made the fibrosis excessive, thus aggravating the adhesion level mentioned above, making it difficult for the intestine to function, and further making it difficult to recover the anastomosis. Therefore, through a series of in vivo biological characterizations of the prepared double-layer stent, it can be found that it has a positive significance for the recovery of the anastomosis after obstruction.

[0190] Summarize

[0191] Complete healing of the intestine after surgery is a long physiological process, which is affected by various factors in the body. Through SEM images, we can observe the unique fiber filaments of PTMC / PHA in the in vivo intestinal scaffolds prepared by us. With its unique structure, it can promote cell adhesion and proliferation. At the same time, the uniform filaments of the antibacterial surface of PVA / OHA-Gs have good conditions for the release of Gs, so that it can play a rapid antibacterial role in the early stage of intestinal healing. At the same time, through mechanical property testing, it was found that these fiber filaments have good flexibility and match the intestine, and the overall biocompatibility. These properties directly or indirectly promote the healing of the intestine after obstruction. Finally, we placed the stent in the intestine and observed that the adhesion degree of the intestinal healing process after the stent was implanted was small, and the burst pressure recovery strength was good. At the same time, the tissue sections can be observed that the tissue healing process conforms to the physiological healing law. From the expression of the degree of inflammation, the expression of new blood vessels and the degree of fibrosis, it can be seen that the flexible and degradable stent with antibacterial coating prepared by us provides good conditions for the healing of obstructed intestinal anastomosis and promotes the healing of the intestine. All these prove that it provides a new way for intestinal anastomosis healing after obstruction. Of course, this still requires a lot of research to promote the further development of intestinal stents.

Claims

1. A double-layered flexible intestinal anastomosis stent with an antibacterial surface, characterized in that: The intestinal anastomosis stent is composed of a PTMC / PHA nanofiber inner layer obtained by blending a homopolymer or copolymer of polytrimethylene carbonate (PTMC) and polyhydroxyalkanoate (PHA) through electrostatic spinning technology, wherein the mass ratio of PTMC to PHA is 9:1-5:5, and an antibacterial outer layer of PVA / OHA-Gs nanofiber obtained by mixed spinning of aldehyded hyaluronic acid (OHA) and polyvinyl alcohol (PVA) and gentamicin sulfate (Gs), wherein the mass ratio of PVA to OHA is 9:1-5:

5. The two-layer structure is composed of the following:

2. The double-layered flexible intestinal anastomosis stent with an antibacterial surface layer according to claim 1, characterized in that: The PVA / OHA-Gs nanofiber is prepared by continuous electrospinning of a mixed spinning solution of OHA, PVA and Gs on the basis of an inner layer of a PTMC / PHA fiber.

3. The double-layered flexible intestinal anastomosis stent with an antibacterial surface layer according to claim 1, characterized in that: The antibacterial outer layer of the PVA / OHA-Gs nanofiber contains 0.1-1.0% Gs.

4. The double-layered flexible intestinal anastomosis stent with an antibacterial surface layer according to claim 1, characterized in that: The thickness of the PTMC / PHA nanofiber inner layer is 0.15-0.4 mm.

5. The double-layered flexible intestinal anastomosis stent with an antibacterial surface layer according to claim 1, characterized in that: The homopolymer or copolymer of polytrimethylene carbonate (PTMC) is one or more of the following: PTMC homopolymer, P(TMC-c-CL) copolymer, P(TMC-c-PDO) copolymer, P(TMC-c-LA) copolymer, P(TMC-c-GA) copolymer and PTMC-b-PEG-b-PTMC copolymer.

6. A method for preparing the double-layered flexible intestinal anastomosis stent with an antibacterial surface layer as claimed in claim 1, characterized in that: The following steps are involved: (1) Synthesis of PTMC: Using TMC monomers through catalytic ring-opening polymerization to synthesize polymer PTMC with a certain molecular weight; (2) Electrospinning after blending PTMC and PHA: Weigh the prepared PTMC and PHA blend and dissolve them in hexafluoroisopropanol (HFIP) solvent to form a spinning solution with a solute concentration of 1.5-5 wt.%, and obtain the PTMC / PHA nanofiber inner layer structure by electrospinning; (3) Synthesis of OHA and determination of hydroformylation degree: OHA was obtained by periodate oxidation of hyaluronic acid (HA) using sodium periodate (NaIO4) as an oxidant, and the hydroformylation degree of OHA was determined by 2,4-dinitrophenylhydrazine reagent (DNPH); (4) Electrospinning after blending PVA, OHA and Gs: Weigh the prepared OHA and PVA and mix them to form a water-soluble spinning solution, then add a certain proportion of Gs into it. After it is completely dissolved, the PVA / OHA-Gs nanofiber antibacterial outer layer is obtained by continuous electrospinning on the basis of the prepared PTMC / PHA nanofiber inner layer.

7. The method for preparing the double-layered flexible intestinal anastomosis stent with an antibacterial surface layer according to claim 6, characterized in that: The concentration of the water-soluble spinning solution in step (4) is 6-10 wt%.

Citation Information

Patent Citations

  • Drug controlled-release double-layer nanofiber wound dressing and preparation method thereof

    CN103990175A

  • Novel intestinal flexible anastomotic stent

    CN113893390A